Averting an oil spill disaster through legal measures and law implementations - Laikram, Siwarut; Pathak, Shubham; Yaseen, Muhammad (Frontiers in Marine Science, 2025)
IntroductionThis paper aims to analyze the various legal perspectives towards the oil spills in the sea and ocean waters that directly or indirectly impact the Thai economy and communities.MethodsThe methodology for this study employs a qualitative approach, collecting data from key informant interviews with respondents selected from the concerned ministries, departments, and other stakeholders involved in the oil spill disaster response, recovery, and policy implementations at the local, national, and international levels. This study relies on primary data such as international, national, and local legal acts, government five-year plans, announcements from relevant ministries, and published government reports, supplemented by secondary data from scholarly literature. The data analysis involves content analysis based upon the legal themes affecting Thailand’s social, economic, and environmental setup, along with Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis.ResultsThe findings reveal a lack of a legal framework for effective oil spill clean-up mechanisms and insufficient resources at all levels of oil spill disaster governance in Thailand. The strict top-to-bottom approach among three-tier cleaning procedures and over-dependence upon the eyewitness to report the incident results in the delay of oil spill response and recovery mechanisms. The laws are found to be lacking in protecting marine life and environmental flora and fauna.DiscussionThe originality of this paper has been enhanced in terms of international conventions, including MARPOL, a recent oil spill case study from Thailand, and current and improved data analysis.